Caffeic Acid Phenethyl Ester Protects Kidney Mitochondria against Ischemia/Reperfusion Induced Injury in an In Vivo Rat Model - Justina Kamarauskaite; Rasa Baniene; Darius Trumbeckas; Arvydas Strazdauskas; Sonata Trumbeckaite (MDPI AG, 2021)
To improve ischemia/reperfusion tolerance, a lot of attention has been focused on natural antioxidants. Caffeic acid phenethyl ester (CAPE), an active component of the resinous exudates of the buds and young leaves of Populus nigra L., Baccharis sarothroides A., etc., and of propolis, possesses unique biological activities such as anti-inflammatory, antioxidant, immunomodulating, and cardioprotective effects, among others. There is a lack of studies showing a link between the antioxidant potential of CAPE and the mechanism of protective action of CAPE at the level of mitochondria, which produces the main energy for the basic functions of the cell. In the kidney, ischemia/reperfusion injury contributes to rapid kidney dysfunction and high mortality rates, and the search for biologically active protective compounds remains very actual. Therefore, the aim of this study was to identify the antioxidant potential of CAPE and to investigate whether CAPE can protect rat kidney mitochondria from in vivo kidney ischemia/reperfusion induced injury. We found that CAPE (1) possesses antioxidant activity (the reducing properties of CAPE are more pronounced than its antiradical properties); CAPE effectively reduces cytochrome c; (2) protects glutamate/malate oxidation and Complex I activity; (3) preserves the mitochondrial outer membrane from damage and from the release of cytochrome c; (4) inhibits reactive oxygen species (ROS) generation in the Complex II (SDH) F site; (5) diminishes ischemia/reperfusion-induced LDH release and protects from necrotic cell death; and (6) has no protective effects on succinate oxidation and on Complex II +III activity, but partially protects Complex II (SDH) from ischemia/reperfusion-induced damage. In summary, our study shows that caffeic acid phenethyl ester protects kidney mitochondrial oxidative phosphorylation and decreases ROS generation at Complex II in an in vivo ischemia/reperfusion model, and shows potential as a therapeutic agent for the development of pharmaceutical preparations against oxidative stress-related diseases.